Relation between heart rate variability and training load in middle-distance runners - Pichot, V.; Roche, F.; Gaspoz, J. M.; Enjolras, F.; Antoniadis, A.; Minini, P.; Costes, F.; Busso, T.; Lacour, J. R.; Barthelemy, J. C. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Monitoring physical performance is of major importance in competitive sports. Indices commonly used, like resting heart rate, O2max, and hormones, cannot be easily used because of difficulties in routine use, of variations too small to be reliable, or of technical challenges in acquiring the data.